2007
DOI: 10.1103/physreve.75.051705
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer interactions and the dependence of biaxiality of the chiral smectic-C*phase on electric field in the helical unwinding process

Abstract: We investigate the unwinding process of pure and racemized mixtures of ͑1-methylheptyloxycarbonyl͒ phenyl-4Ј-carboctyloxy-biphenyl-4-carboxylate ͑MHPOOCBC͒ in homeotropic cells by studying ͑i͒ the optical texture under crossed polarizers and ͑ii͒ the tilted conoscopy as a function of the electric field for different temperatures. The tilted conoscopy yields biaxiality and the tilt angle for values of the latter up to 45°. We find that the unwinding process depends on the optical purity of the sample and the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
(1 reference statement)
1
13
0
Order By: Relevance
“…However, the mechanism for the occurrence of the helical fracture is not clear, and it is difficult to estimate the electric field required to generate helical fractures at this state. As reported in our previous paper [9], we observed that the electric field, at which the helical fracture occurs, varies according to the enantiomeric excess ratio in the racemized mixtures. This implies that the material parameters such as the spontaneous polarization, pitch and the interlayer interactions might affect the emergence of the helical fracture.…”
Section: -P4supporting
confidence: 55%
See 4 more Smart Citations
“…However, the mechanism for the occurrence of the helical fracture is not clear, and it is difficult to estimate the electric field required to generate helical fractures at this state. As reported in our previous paper [9], we observed that the electric field, at which the helical fracture occurs, varies according to the enantiomeric excess ratio in the racemized mixtures. This implies that the material parameters such as the spontaneous polarization, pitch and the interlayer interactions might affect the emergence of the helical fracture.…”
Section: -P4supporting
confidence: 55%
“…The electric field for the emergence of the domain walls corresponds exactly to the step-like increase of the selective reflection peak. The domain walls have single sharp lines and propagate independently of each other indicating that these are π walls propagating along layers [9]. π walls always accompany with the helical fractures as shown in fig.…”
Section: -P1mentioning
confidence: 93%
See 3 more Smart Citations